2020
DOI: 10.1007/s40670-020-00946-9
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Clinical Reasoning During a Simulated Viral Pandemic: Evidence of Cognitive Integration and Insights on Novices’ Approach to Diagnostic Reasoning

Abstract: Introduction Cognitive integration from multiple disciplines is essential to clinical problem-solving. Because it is not directly observable, demonstrating evidence of learners' cognitive integration remains a challenge. In addition, little is known about preclinical medical students' approach to diagnostic reasoning despite widespread implementation of clinical reasoning curricula for these early learners. The objectives of this study were to characterize how first-year medical students integrated knowledge t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Students tended to use a compare-contrast analytical approach to diagnostic reasoning, with a smaller subset also employing a causal approach. 33 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Students tended to use a compare-contrast analytical approach to diagnostic reasoning, with a smaller subset also employing a causal approach. 33 …”
Section: Resultsmentioning
confidence: 99%
“…To evaluate students' engagement with the learning content and their performance of learning objectives 1–6, we qualitatively analyzed students' team reports by performing a content analysis. 33 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, students dominantly use the type 2 clinical reasoning process as novices or beginners [ 10 ]. Previous research has indicated that novices employ a pathophysiological analytic method for diagnosis more frequently than a pattern recognition technique, which develops after trainees establish substantial illness scripts through exposure or clinical experience [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from other non-communicable diseases, evaluation of cognitive impairment is obligatory, as this population is essential to anticipate and diagnose the clinical conditions in routine clinical postings, which depends on their cognitive skills. 11 Body Mass Index (BMI) is a simple, low-cost variable that determines the health status of an individual. 12,13 There is paucity in the literature on the association of BMI and cognitive tasks among young medical students, especially in the Indian population.…”
Section: Introductionmentioning
confidence: 99%